МЕДИЦИНСКИЙ ЦЕНТР БИОЭНЕРГОРЕАБИЛИТАЦИИ «АЗИЯ МЕДKZ» В КАЗАХСТАНЕ (Медицинский центр биоэнергореабилитации«Азия МедKZ» (Experimental biology, 2015)
The part of the program of “Nevada-Semipalatinsk” International antinuclear movement is realized. This program about liquidation of consequences of harmful factors for health of the population which have suffered from nuclear tests on nuclear ranges of Semipalatinsk and Lob-Nor (China). The centre of bioenergetic rehabilitation which has helped more than 30000 persons is created.